Finite element modeling of multiphase flows with their balancing while setting the working pressure on wells during oil production - Ovchinnikova, Anastasia S.; Patrushev, Ilya I.; Grif, Alexander M.; Persova, Marina G.; Soloveichik, Yuri G. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2022)
Approaches to modeling multiphase flow in oil reservoir while setting the working pressure for the perforation zones of active wells are considered. The proposed numerical method is based on an implicit calculation of the pressure and an explicit recalculation of the phase saturations in the mesh cells at each time step. Description of the mathematical model, general computational scheme, finite element approximation of the pressure field are presented. To ensure conservation of the mixture flows, special method of balancing is used, and its algorithm is presented. The studies were carried out on the problem of the comparative project SPE-10, for which the calculation of flows for the perforated zones of wells with a set pressure was carried out using two approaches.